PREDICTORS OF DISABILITY IN HEMODIALYSIS PATIENTS - Teovska, Biljana; Trjaceska, Lada; Mladenovska, Daniela; Trajkovski, Vladimir; Sikole, Aleksandar (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Introduction: The aim of this study was to search for predictors of disability among patients treated with hemodialysis. Material and methods: Disability was assessed with self-reports of activities by Katz, Nagi and Rosow-Breslau (R-B) scale in 134 hemodialysis patients in a cross-sectional study. Sociodemographic, clinical, nutritional and dialysis factors were investigated as influencing factors. Multiple logistic regression analysis was used to identify predictors associated with disability scores. Results: Mean Katz, Nagi and R-B scores of the study group were: 4.67 Â± 8.0, 9.96 Â± 7.5, 3.84 Â± 2.4, respectively. In the univariate analysis, women, patients who were older than 65, had diabetes, intradialytic hypotension, catheter as vascular access, sensor or loco-motor problems, carpal-tunnel syndrome, cerebrovascular disease and body mass index more than 31kg/m 2 , had at least one Katz activity impairment. In the multivariate regression model, the older age, female gender, carpal tunnel and catheter presence were the strongest independent predictive markers for Katz impairments. As for Nagi and R-B scales, presence of catheter emerged among the strongest predictors. Conclusion: Many modifiable factors contribute to disability in hemodialysis patients. Interventions are needed before start of hemodialysis in order to unable development of disability during dialysis treatment.